First-in-Family Students, University Experience and Family Life Motivations, Transitions and Participation - O'Shea, Sarah (Springer Nature, 2024)
This open access book, now in its second edition, offers a comprehensive overview of the experiences of First in Family (FiF) or first-generation students in higher education. It draws upon narratives of students and their family members and spans the entire university student life cycle (pre-entry, commencement, progression and graduation) with a focus on specific cohorts including mature-aged students, parents or carers, as well as the differentiated experiences of male and female learners. With research drawn from three major research projects and including over 650 FiF students from across all Australian states and territories, as well as Europe, this wealth of perspectives provides unique insights into the lived reality of attending university in contemporary higher education settings. The book is written for a broad audience and will appeal to those working in universities, as well as family members and students who may be contemplating participating in higher education.